Implementasi Manajemen Sumber Daya Tenaga Pendidikan Terhadap Kualitas Layanan Pendidikan Di MA Hidayatul Mubtadi’in Jati Agung - Mustafida (Advances In Education Journal, 2025)
This study aims to analyze the implementation of educational staff resource management on the quality of educational services at MA Hidayatul Mubtadi’in Jati Agung. Educational staff resource management includes planning, recruitment, development, evaluation, and welfare of educators. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and verification techniques. This study aims to analyze the effectiveness of teacher and education staff management in improving the quality of education. The research methods used include interviews, observations, and documentation studies with samples of teachers, madrasah principals, and education staff. The research findings show that transparent management in recruitment, routine coaching, and objective performance assessments contribute significantly to improving the quality of education. Adaptive and innovative management encourages madrasahs to become pioneers in various educational innovations. The contribution of this study provides an effective management model that can be adopted by other madrasahs to improve the quality of education as a whole